2018
DOI: 10.4314/iijikm.v9i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social media use on the reading habits of selected high school students in Nigeria

Abstract: The study investigates the effect of social media use on the reading habits of high school students: a case study of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…It is true that we read school textbooks, but it is not considered as reading but just as a duty (assignment)". Akande and Oyedapo (2018) recommend that schools should establish reading clubs in collaboration with English language teachers and school librarians.…”
Section: School Reading Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is true that we read school textbooks, but it is not considered as reading but just as a duty (assignment)". Akande and Oyedapo (2018) recommend that schools should establish reading clubs in collaboration with English language teachers and school librarians.…”
Section: School Reading Activitiesmentioning
confidence: 99%
“…This explains why these girls go to libraries to buy books and not to sit and read there. With this line, Akande and Oyedapo (2018) recommended that countries' policymakers should consider building modern libraries equipped with 21 st -century technological facilities and stocked with a wide range of reading materials. Merga (2017) believed that making books accessible denotes the value of books and reading.…”
Section: Home Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…However, [9] found that the pupils are exposed to a wide range of ICT gadgets and used them for leisure or socialising than for academic purposes. Furthermore, studies shown that pupils spent more time on the use of social media, especially with the affordability of gadgets, thereby causing less time spent on reading and cultivating good reading habits [10]- [12]. In addition, Malaysian pupils often use social media for both positive and negative [13].…”
Section: A Social Mediamentioning
confidence: 99%
“…Reading is essential for a good learning process (Cuadro et al, 2021). Language and word reading abilities affect reading comprehension (Akande & Oyedapo, 2018 Irvin, 2015;Kirschmann et al, 2021;Perfetti, 2007). Reading skills are essential in the era of information technology (Ningsih, 2016;Suwannee & Siripan, 2021).…”
Section: Introductionmentioning
confidence: 99%